Penilaian Kepuasan Konsumen ditinjau dari Kualitas Produk, Lokasi dan Kualitas Pelayanan pada Depot Leko Tulungagung - Gesty Ernestivita; Arizky Saputro; Subagyo Subagyo (POLITEKNIK CAHAYA SURYA, 2021)
The competitive condition of the culinary world is currently weakening, this is due to various factors affecting economic activity, one of which is influenced by the Covid 19 pandemic. Depot Leko Tulungagung is one type of business that produces food products that also struggle to exist during the pandemic. Ideally, consumers who buy food get a sense of satisfaction, both in terms of product quality (food), location, and service. The purpose of this study was to analyze and determine: the significant influence between product quality on customer satisfaction Depot Leko Tulungagung (2) the significant effect between location on customer satisfaction Depot Leko Tulungagung (3) significant influence between service quality on customer satisfaction Depot Leko Tulungagung (4) significant influence between product quality, location, and service quality on customer satisfaction Depot Leko Tulungagung. The approach in this study uses a quantitative approach with causal research techniques. The data collection by distributing questionnaires. The sample used was 40 respondents. The sampling technique used is incidental sampling technique. The data analysis technique used multiple linear regression analysis with SPSS for windows version 23 software. The conclusions of this study are (1) There is a partially significant effect between product quality and consumer satisfaction at Depot Leko Tulungagung. (2) There is a partially significant effect between locations on customer satisfaction at Depot Leko Tulungagung. (3) There is a partially significant influence between service quality and customer satisfaction at Depot Leko Tulungagung. (4) There is a significant effect simultaneously between product quality, location, and service quality on customer satisfaction at Depot Leko Tulungagung. Keywords: Product Quality, Location, Service Quality, Customer Satisfaction.